Climatic Region and Vine Structure: Effect on Pinotage Wine Phenolic Composition, Total Antioxidant Capacity and Colour - de Beer, D.; Joubert, E.; Marais, J.; van Schalkwyk, D.; Manley, M. (South African Journal of Enology and Viticulture, 2017)
The phenolic composition, total antioxidant capacity (TAC) and colour of Pinotage wines of the 2001, 2002 and 2003 vintages were investigated, using spectrophotometric, high-performance liquid chromatography (HPLC), free radical scavenging and objective colour analyses. Grapes were harvested from grapevines in three climatic regions ranging from cool to warm, with bush (20- and 30-cm trunk height) and trellised (30- and 60-cm trunk heights) vine treatments, on several vineyard sites in each climatic area. Climatic region had a significant effect on the content of several phenolic compounds; the concentration of anthocyanin monoglucosides, flavonols, flavan-3-ols and tartaric acid esters of hydroxycinnamic acids generally increased as the climatic region becomes cooler, while concentrations of acylated derivatives and free hydroxycinnamic acids decreased. Wines made from bush vines contained higher concentrations of flavonols, gallic acid and flavan-3-ols than those from trellised vines, but lower concentrations of some anthocyanin monoglucosides and acylated derivatives, as well as non-coloured polymers. These trends resulted in differences in TAC and objective colour parameters, although the different vintages did not show the same trends in all cases. More vintages should therefore be investigated to clarify these effects. Wines from the cool climatic regions and from bush vines were generally darker coloured, with higher TAC than those from the warm climatic regions and bush vines, respectively. High TAC, therefore, coincided with higher colour quality. Variations in TAC were partly explained by trends for individual phenolic compounds, although unknown compounds played a major role.